12345678901011121314151617181920
Attachments:
![](https://hi-static.z-dn.net/files/df4/7f7f08e3818184ed9f9044a666f2ce2e.jpg)
Answers
Answered by
0
Answer:
vsigdiyeigzigd8ydogs8tdogsite8tq7rq7tsohfohfitw7rau42752852528540749
Answered by
0
cosA/1+sinA. + 1+sinA/cosA. =2sec A
LHS: cos2A+(1+sin2A)/(1+sinA)cosA. [(a+b2=a2+b2+2ac]
=cos2A+1+2sinA+sin2A/(1+sinA)cosA
=cos2A+sin2A+1+2sinA/(1+sinA)cosA
=1+1+2sinA/(1+sinA)cosA. [cos2A+sin2A=1]
=2+2sinA/(1+sinA)cosA
=2/cosA=2secA =RHS
Hence Proved
Similar questions